Biochemistry of lipids, lipoproteins, and membranes - Vance, Dennis E.; Vance, Jean E. (New comprehensive biochemistry ;, 1991)
The second edition of this book on lipids, lipoprotein and membrane biochemistry has two major objectives - to provide an advanced textbook for students in these areas of biochemistry, and to summarise the field for scientists pursuing research in these and related fields. Since the first edition of this book was published in 1985 the emphasis on research in the area of lipid and membrane biochemistry has evolved in new directions. Consequently, the second edition has been modified to include four chapters on lipoproteins. Moreover, the other chapters have been extensively updated and revised.